Equipment for determining the parameters of thermoelectric cooling modules - Anatychuk , L.I.; Havryliuk, M. V.; Lysko, V.V. (Journal of Thermoelectricity, 2021)
The results of the development of the design of equipment for measuring the parameters of thermoelectric cooling modules, as well as determining the thermoelectric properties of materials in these modules, are presented. The equipment was created on the basis of the absolute method, which makes it possible to determine the parameters of modules in real conditions of their operation and allows instrumental minimization of the main sources of measurement errors. The measurement control unit is built on the basis of a multichannel analog-to-digital converter. Processing and display of measurement results are carried out using a computer; the results are displayed through graphs and tables. Bibl. 5, Fig. 6.